2010
DOI: 10.1007/s12307-010-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of the Pro-apoptotic Gene PAR-4 During the Morphogenesis of MCF-10A Human Mammary Epithelial Cells

Abstract: The histological organization of the mammary gland involves a spatial interaction of epithelial and myoepithelial cells with the specialized basement membrane (BM), composed of extra-cellular matrix (ECM) proteins, which is disrupted during the tumorigenic process. The interactions between mammary epithelial cells and ECM components play a major role in mammary gland branching morphogenesis. Critical signals for mammary epithelial cell proliferation, differentiation, and survival are provided by the ECM protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Moreover, the search for potential downstream targets showed that the HOXB7overexpressing cells, along with decreased CTNNB1 expression, presented enriched direct interaction of HOXB7 with the promoter regions of EGFR, DNMT3B, COMMD7, and CDH1 (Figure 7). The maintenance of breast cells on a reconstituted basement membrane results in a 3D-growth that recapitulates several aspects of glandular architecture in vivo that are lost in 2D culture, as demonstrated with MCF10A cells [21,34]. Interestingly, MDA231 HOXB7overexpressing cells (D3) formed smaller and more compact spheroids compared to the spread and branched growth shown by the control cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the search for potential downstream targets showed that the HOXB7overexpressing cells, along with decreased CTNNB1 expression, presented enriched direct interaction of HOXB7 with the promoter regions of EGFR, DNMT3B, COMMD7, and CDH1 (Figure 7). The maintenance of breast cells on a reconstituted basement membrane results in a 3D-growth that recapitulates several aspects of glandular architecture in vivo that are lost in 2D culture, as demonstrated with MCF10A cells [21,34]. Interestingly, MDA231 HOXB7overexpressing cells (D3) formed smaller and more compact spheroids compared to the spread and branched growth shown by the control cells.…”
Section: Discussionmentioning
confidence: 80%
“…The maintenance of breast cells on a reconstituted basement membrane results in a 3D-growth that recapitulates several aspects of glandular architecture in vivo that are lost in 2D culture, as demonstrated with MCF10A cells [ 21 , 34 ]. Interestingly, MDA231 HOXB7-overexpressing cells (D3) formed smaller and more compact spheroids compared to the spread and branched growth shown by the control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Normal human epithelial MCF10A and 184hTERT cells were cultured as described previously. 46,47 To examine Rictor phosphorylation, cells were serum starved for 24 h, then treated with or without 10% fetal bovine serum for 30 min. Cells were incubated with QLT0267 at concentrations specified in the text (QLT, Vancouver, BC, Canada), LY294002 (Sigma-Aldrich, Oakville, ON, Canada) or rapamycin (LC Laboratories, Woburn, MA, USA), 5 h, 1 h and 30 min.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…NMuMG and MCF-10A cell lines possess morphogenic capabilities when resuspended and cultured in a 3-D matrix like collagen [16] , [19] . AG1478 had a dramatic effect on 3D-morphogenesis of both cell lines, inducing death of all cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%